Análise toxicológica, citotóxica e mutagênica de extratos aquosos de Aspidosperma pyrifolium (Apocynaceae) - Costa, Edigleyce de Lima (2015)
The Aspidosperma pyrifolium Mart species. it is used in feed for farm ani-mals. However, there are few studies on the toxicity of this plant. This study aimed to iden-tify the existence of toxic effect, cytotoxic and mutagenic leaves of A. pyrifolium the test system Allium cepa and mice. It was made growth analysis of roots, inhibition relative and mitotic index with the Allium cepa test. For the LD50 they were used of groups mice were observed for 14 days to determine the number of dead and surviving animals. For the mi-cronucleus test and binucleated cells was done extracting bone marrow of animals. Bioas-says performed with the Allium cepa revealed that the aqueous extract of dried leaves showed no toxic effects, however, stimulated cell division in a concentration of 50 mg/L, is indicative of formation of tumor cells. The fresh leaves were toxic at the concentration of 300 mg/L and had a effect toxic sublethal on concentration of 5 mg/L.. In mice, the median lethal dose was 750.63 mg/kg with the aqueous extract of fresh leaves, and lethal concen-trations tested from the concentration 900 mg/kg in males and females. The evaluated ani-mals showed behavioral changes in the nervous system and change in average total weight. The concentrations tested indicated are not mutagenic or not cytotoxic in the overall analy-sis of micronucleus frequency and binucleated cells, respectively. But, this work provides data toxicity; cytotoxicity and mutagenicity still have not investigated for the species A. pyrifolium